(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Successfully tailored new types of nanocrystalline Mn-Mo-Sn-W-O and Mn-Mo-Sn-W-Sb-O electrocatalysts on the intermediate layer of Ir1-x-ySnxSbyO2+0.5y on titanium metal substrate for the production of hydrogen gas from electrolysis of 0.5 M NaCl solution of pH 1 at very high current density of 1000 A.m-2 with forming less than 0.3 % of the environmentally harmful chlorine. Antimony and tungsten additions are more effective for better durability of both the electrodeposited Mn-Mo-Sn-X(X=Sb,W)-O/Ir1-x-ySnxSbyO2+0.5y/Ti anodes than that of Mn-Mo-Sn-O/Ir1-x-ySnxSbyO2+0.5y/Ti anode for long period electrolysis of acidic 0.5 M NaCl solution to produce hydrogen. The high oxygen evolution efficiency (OEE) of the quadrate or more oxides electrocatalysts (i. e., 99.7-99.9 % OEE) maintained during prolonged electrolysis and even after electrolysis for five or more months. The Mn-Mo-Sn-X(X=Sb,W)-O/Ir1-x-ySnxSbyO2+0.5y/Ti anodes showed about 99.7-99.9 % of oxygen evolution efficiency. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11459 Bangladesh J. Sci. Ind. Res. 47(2), 231-238, 2012